2020
DOI: 10.7150/ijbs.49785
|View full text |Cite
|
Sign up to set email alerts
|

Oleate acid-stimulated HMMR expression by CEBPα is associated with nonalcoholic steatohepatitis and hepatocellular carcinoma

Abstract: Non-alcoholic steatohepatitis (NASH) is a type of nonalcoholic fatty liver disease and has become a major risk factor for hepatocellular carcinoma (HCC). However, the underlying pathophysiological mechanisms are still elusive. Here, we identify hyaluronan-mediated motility receptor (HMMR) as a critical gene associated with NASH/HCC by combination of bioinformatic analysis and functional experiments. Analysis of differentially expressed genes (DEGs) between normal controls and NASH/HCC identified 5 hub genes (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…By analyzing microarray data, UBE2T was considered a hub gene in patients with gallbladder cancer, and it might serve as a biomarker for gallbladder cancer [50]. rough the PI3K/Akt signaling pathway and the Akt/GSK3β/β-catenin pathway, UBE2T is involved in the cell proliferation, migration, and invasion of cancer cells [51][52][53]. UBE2NL, also a ubiquitin-conjugating enzyme E2 family member, is related to the ubiquitination process [54].…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing microarray data, UBE2T was considered a hub gene in patients with gallbladder cancer, and it might serve as a biomarker for gallbladder cancer [50]. rough the PI3K/Akt signaling pathway and the Akt/GSK3β/β-catenin pathway, UBE2T is involved in the cell proliferation, migration, and invasion of cancer cells [51][52][53]. UBE2NL, also a ubiquitin-conjugating enzyme E2 family member, is related to the ubiquitination process [54].…”
Section: Discussionmentioning
confidence: 99%
“…The RNA samples from the cells or the tumor tissues were extracted and reverse transcribed into cDNA according to the manufacturer’s instructions (Thermo Fisher Scientific, Waltham, MA, USA) ( 26 28 ). Then, the cDNA samples were analyzed by quantitative PCR (qPCR) according to the manufacturer’s instructions (Thermo Fisher Scientific, Waltham, MA, USA) and methods described in previous publications ( 26 28 ). Primers used in the present work were listed as follows: (1) FBI-1, forward sequence, 5’-GCAACATCTGCAAGGTCCGCTT-3’; reverse sequence, 5’-TCTTCAGGTCGTAGTTGTGGGC-3’; (2) miR-3692-5p, the reverse-transcription primer, 5’-GTCGTATCCAGTGCGTGTCGTGGAGTCGGCAATTGCACTGGATACGACCAGTAT-3’; forward sequence, 5’-CCTGCTGGTCAGGAGTGGATACTG-3’; reverse sequence, 5’-CAGTGCGTGTCGTGGAGT-3’; (3) HIF-1α, forward sequence, 5’-TATGAGCCAGAAGAACTTTTAGGC-3’; reverse sequence, 5’-CACCTCTTTTGGCAAGCATCCTG-3’; (4) GLUT1, forward sequence, 5’-TTGCAGGCTTCTCCAACTGGAC-3’; reverse sequence, 5’-CAGAACCAGGAGCACAGTGAAG-3’; (5) LDHA, forward sequence, 5’-GGATCTCCAACATGGCAGCCTT-3’; reverse sequence, 5’-AGACGGCTTTCTCCCTCTTGCT-3’; (6) N-cadherin, forward sequence, 5’-CCTCCAGAGTTTACTGCCATGAC-3’; reverse sequence, 5’-GTAGGATCTCCGCCACTGATTC-3’; (7) E-cadherin, forward sequence, 5’-GCCTCCTGAAAAGAGAGTGGAAG-3’; reverse sequence, 5’-TGGCAGTGTCTCTCCAAATCCG-3’; and (7) Vimentin, forward sequence, 5’-AGGCAAAGCAGGAGTCCACTGA-3’; reverse sequence, 5’-ATCTGGCGTTCCAGGGACTCAT-3’.…”
Section: Methodsmentioning
confidence: 99%
“…For the animal experiments, the subcutaneous tumor tissues were collected and grinded by using the liquid nitrogen. The RNA samples from the cells or the tumor tissues were extracted and reverse transcribed into cDNA according to the manufacturer's instructions (Thermo Fisher Scientific, Waltham, MA, USA) (26)(27)(28). Then, the cDNA samples were analyzed by quantitative PCR (qPCR) according to the manufacturer's instructions (Thermo Fisher Scientific, Waltham, MA, USA) and methods described in previous publications (26)(27)(28).…”
Section: Quantitative Polymerase Chain Reaction and Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, very little research can be found about GINS2 in the liver, especially in NAFLD. Previous bioinformatics studies indicated that GINS2 might be the hub genes in the development of NASH to HCC and predicted poor prognosis in HCC, but there was no further experiment to verify its effects on NAFLD (Lian et al, 2018;Zhang et al, 2020). PDLIM3, highly expressed in skeletal and cardiac muscle, has been suggested to play a pivotal role in myocyte stability, signal transduction, and mechanical signaling, especially in growth and remodeling processes (Zheng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%